Pengembangan Aplikasi Penjualan Toko Wulan berbasis Web menggunakan Api Midtrans sebagai Payment Gateway - Indah M., Laura G.; Putra, Widhy Hayuhardhika Nugraha; Purnomo, Welly (Jurnal Pengembangan Teknologi dan Ilmu Komputer, 2022)
Wulan Store is one of the food shops in Boyolali City that provides a variety of daily basic needs that serve retail and wholesale sales. In addition, this store also provides services for the delivery of goods ordered by customers to the desired address. However, until now ordering goods and buying and selling transactions are still done manually, namely visiting the store and paying directly. The mechanism for payment and ordering of goods is not yet effective, because it causes long queues at the store. To make buying and selling transactions easier at the Wulan Store, a sales application that is integrated with the Midtrans payment gateway was developed. Customers will find it easier to make payments without having to confirm to the admin, as well as make it easier to order goods without having to come directly to the store. In doing development, analysis and design are needed to determine functional and non-functional requirements on the system, namely using UML diagrams and database design using Physical Data Model (PDM). The development of this system is carried out using the waterfall model, CodeIgniter framework, MySQL DBMS. The test is carried out using the blackbox testing method to get 100% valid results, which means the system can run in accordance with the specified requirements analysis, compatibility testing obtains that the system is compatible so that it can be run on various types of browsers, System Usability Scale (SUS) which obtains the final calculation results. usability evaluation with an average SUS value of 78. This shows that the usability level of the Wulan Store sales application can be accepted and used easily by users.